(untitled) (Minerva, 2019)
Epistle 4 (11 for the former editors), in Braulio of Zaragoza’s Epistolarium, was addressed to the then presbyter Taio. It has been frequently used to support the existence of a lost work by Taio. Such a theory has no basis, and arguments will be given to refute it. Likewise, the analysis of the whole of the epistle reveals its fundamentally moralizing aim, with an important influence of Jerome’s epistle 50.